Gamifikasi dalam Industri Ojek Online: Pengaruh terhadap Perlindungan dan Kesejahteraan Pekerja - Muhammad Syaihuputra, Brian Maulana; Fauzyyah, Nabilah Putri; Aritonang, Christian Daniel; Tiffany Putri, Gabriela (Forschungsforum Law Journal, 2025)
Gamification has become a core strategy in the online taxi industry, implemented to enhance driver performance through incentive systems, point accumulation, and rankings. While it provides flexibility and income opportunities, this system often results in unfair working conditions, including extended working hours, income instability, and inadequate social protection. Utilizing a library research approach and normative juridical analysis, this study assesses the impact of gamification on worker welfare and identifies regulatory loopholes in their legal protection. The findings indicate that the partnership status weakens drivers' bargaining power, while algorithmic systems restrict their control over work. Consequently, more transparent regulations and labor protection policies that are responsive to platform-based work models are necessary.